'The Government Should Be Ashamed': On the Possibility of Organisations' Emotional Duties. (November 2018) - Collins, Stephanie
When we say that 'the government should be ashamed', can we be taken literally? I argue that we can: organisations have duties over their emotions. Emotions have both functional and felt components. Often, emotions' moral value derives from their functional components: from what they cause and what causes them. In these cases, organisations can have emotional duties in the same way that they can have duties to act. However, emotions' value partly derives from their felt components. Organisations lack feelings, but can have duties to increase the likelihood that their members have relevant emotions (with the right felt components), in virtue of and in accordance with their role in the organisation. To systematise these conclusions, I provide a taxonomy of organisations' – and individuals' organisationally situated – emotional duties. This taxonomy will enable scholars of electoral politics, international politics and public policy to systematically integrate emotions into the study of organisations.